An investigation into rank reversal properties of the multiplicative AHP. (1st January 2011) - Ramanathan, Usha; Ramanathan, Ramakrishnan
The multiplicative analytic hierarchy process (MAHP) has been proposed in response to some perceived shortcomings of the traditional version of the analytic hierarchy process (AHP). This paper joins a series of articles that investigated the rank reversal issue in the context of MAHP. In general, many of the previous articles did not highlight their interpretation of MAHP properly. In this paper, we consider MAHP as suggested by one of the proponents of the methodology and highlight three important operations that distinguish MAHP from its traditional counterpart. We further discuss three sets of simulation experiments to study the rank reversal properties of MAHP. Results indicate that MAHP possesses desirable rank reversal properties.